Population pharmacokinetics of anidulafungin in ICU patients assessing inter‐ and intrasubject variability. Issue 3 (24th July 2020) - Kapralos, Iasonas; Mainas, Efstratios; Apostolopoulou, Olympia; Siopi, Maria; Neroutsos, Efthymios; Apostolidi, Stella; Dimopoulos, George; Sambatakou, Helen; Valsami, Georgia; Meletiadis, Joseph; Dokoumetzidis, Aristides
Abstract : Aims: The population pharmacokinetics (PK) of anidulafungin in critically ill patients hospitalized in intensive care units (ICUs) was explored with the intention of evaluating and optimizing dosing regimens. Methods: A PK study was conducted in a cohort of 13 patients treated with anidulafungin using intensive sampling during multiple periods per patient and the high‐performance liquid chromatography method for drug quantification. A population PK model was developed to describe the concentration‐time course of anidulafungin and the inter‐individual (IIV) and interoccasion variability (IOV) of the PK parameters. Model‐based PK simulations have been performed to estimate the probability of target attainment (PTA), given the pharmacokinetic/pharmacodynamic target of free 24‐hour area under the free drug concentration‐time curve over minimum inhibitory concentration for several dosing regimens. Results: A two‐compartment PK model, with first‐order elimination, best described the data with population clearance (CL) and central/peripheral volume of distribution (V1/V2) of 0.778 L/h and 10.2/21.1 L, respectively, and a mean ± s.d. AUC0‐24 of 119.97 ± 46.23 mg·h/L. Pronounced IIV and IOV variability was found for CL (38% and 31%) and V1 (47% and 30%), respectively. Sequential Organ Failure Assessment (SOFA) and Body Mass Index (BMI) were found to be covariates on CL and V1, respectively. Low PTA values were calculated for borderline Clinical & Laboratory Standards Institute (CLSI)‐susceptible Candida strains. Conclusions: Although anidulafungin exposure was found comparable to that in healthy volunteers, elevated interindividual and significant interoccasion variability was found in critically ill ICU patients, which resulted in reduced PTA values in these patients.